2018
DOI: 10.1080/14767058.2018.1487940
|View full text |Cite
|
Sign up to set email alerts
|

The Japanese experience and pharmacokinetics of antenatal maternal high-dose immunoglobulin treatment as a prophylaxis for neonatal hemochromatosis in siblings

Abstract: This treatment prevented the recurrence of NH in siblings in Japanese women. We examined the details of serum IgG concentrations and introduced a new pharmacokinetic simulation model of IgG concentrations during IVIG treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…2 Consistent with the alloim-mune mechanism, GALD exhibits high recurrence rates up to 90% in pregnancies that can be prevented by antenatal intravenous immunoglobulin (IVIG) treatment. 1,[3][4][5] In the present study, we reported two cases with GALD recurrence that was prevented by antenatal IVIG treatment in the second trimester.…”
supporting
confidence: 47%
See 1 more Smart Citation
“…2 Consistent with the alloim-mune mechanism, GALD exhibits high recurrence rates up to 90% in pregnancies that can be prevented by antenatal intravenous immunoglobulin (IVIG) treatment. 1,[3][4][5] In the present study, we reported two cases with GALD recurrence that was prevented by antenatal IVIG treatment in the second trimester.…”
supporting
confidence: 47%
“…The current treatment consists of antenatal IVIG (1 g•kg -1 ) administrations at 14, 16, 18 WG and contin-ued weekly to the end of pregnancy. 1,[3][4][5] It seems to be crucial to continue treatment until at least the 35 WG, for a total of 20 doses; whereas, the recommended dose is 60 g considering the side effects and the required infusion time. 1 It is important to note that in both of the presented cases, the treatment was initiated later than the recommended gestational week due to late admission to our clinic.…”
Section: Discussionmentioning
confidence: 99%
“…One child whose mother did not receive immunoglobulin treatment who underwent LDLT from the puerperal mother developed neonatal hemochromatosis. Antenatal maternal high-dose intravenous immunoglobulin treatment has been reported to be effective for preventing neonatal hemochromatosis recurrence [ 30 ]. In younger siblings of patients with OTCD, carbamoyl phosphate synthetase 1 deficiency, MMA, and Niemann-Pick disease type C, 4 of the mothers had prenatal amniocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data show that once a woman has given birth to a baby with GALD, there is approximately 80-95% risk that the subsequent babies will also suffer from GALD, even with another father [14][15][16]. Others have reported a recurrence rate of approximately 70% [17].…”
Section: Introductionmentioning
confidence: 99%